Penggunaan Aplikasi Wayground untuk Meningkatkan Kemampuan Bahasa Indonesia Baku bagi Peserta Didik Kelas X SMK Al-Falah Tanjungjaya - Siti Papat Patimah; Zakia Nur Huda; Trisa Nurfitri; Yuni Ertinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The objective of this study is to improve the ability to use formal and informal language for students at SMK Al-Falah Tanjungjaya as one of the strategies for fostering the Indonesian language. In this study, there are several main focuses, namely the use of formal and informal language by students at SMK Al-Falah Tanjungjaya and the integration of Wayground learning media in Indonesian language learning. This study uses service learning techniques and descriptive research data analysis techniques. The steps carried out in this study include (1) conducting guidance on the use of formal and informal language at SMK Al-Falah Tanjungjaya, (2) analyzing the data results from the guidance, (3) classifying the data results from the guidance, (4) interpreting the data results from the guidance, and (5) developing and concluding the results of the guidance data analysis. The results of the data analysis indicate that the use of Wayground can help improve student understanding.